1987
DOI: 10.5271/sjweh.2012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to vehicle exhaust on health.

Abstract: M. Effe cts of exposure to vehicle exhaust on health . Scand J Work En viron Health I3 (1987) 505-512. Exposure to combustion engine exhaust and its effect on crews of roll-on roll-off ships and car ferries and on bus garage staff were studied. The peak concentration s recorded for some of the substa nces stu died were as follows: total part iculate s (diesel only) 1.0 rng/rn" , benzene (diesel) 0.3 mg/rn ", form aldehyde (gasoline and diesel) 0.8 mg/rn ", and nitrogen dioxide (diesel) 1.2 mg/m'. The highest o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 12 publications
3
27
0
1
Order By: Relevance
“…However, in an earlier study there were no differences in the prevalence of respiratory symptoms between tunnel and turnpike workers, although both may have been highly exposed (65). A small study of 89 workers on roll-on roll-off ships, car ferries, and a bus garage showed significant FEV 1 and FVC decrements during workdays after several days with no exposure (66).…”
Section: Occupational Evidence For Respiratory Effects Of Dementioning
confidence: 99%
“…However, in an earlier study there were no differences in the prevalence of respiratory symptoms between tunnel and turnpike workers, although both may have been highly exposed (65). A small study of 89 workers on roll-on roll-off ships, car ferries, and a bus garage showed significant FEV 1 and FVC decrements during workdays after several days with no exposure (66).…”
Section: Occupational Evidence For Respiratory Effects Of Dementioning
confidence: 99%
“…Respiratory disease has been diagnosed for tunnel workers, but it is not clear which exposures cause the effects (6). Several agents could be implicated (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…The motor pump operator was exposed to toluene and formaldehyde at concentrations below OELs. The source of these compounds could have been emissions from the vehicle fires or diesel exhaust from the fire apparatus [Ulfvarson et al 1987;Smith et al 2004;Mabilia et al 2006]. For the other fire fighters, the PBZ concentrations we reported represent potential inhalation exposures due to the added protection of the SCBAs they wore.…”
Section: Results (Continued)mentioning
confidence: 99%